Role of high resolution ultrasonography in leprosy - Kush Dugad; Satish Pathak; Rajul Rastogi (Asian Journal of Medical Sciences, 2022)
Background: Ultrasonography is a safe and cost-effective modality to assess gross morphological changes in nerves non-invasively. Early diagnosis will allow the early institution of therapy and arrest the progression of the disease thus, helping in decreasing disability grading. Aims and Objectives: The aim of the study was to assessing the role of high resolution ultrasonography (HRUS) in leprosy. The objectives of the study were to detect sonographic changes in nerves in leprosy patients, and to detect neural complications by sonography in leprosy patients. Materials and Methods: The study was conducted over 18 months from the year 2020–2021 at ‘Teerthanker Mahaveer Medical College and Research Centre, Moradabad. A total of 37 patients were included in our study. HRUS was performed on the bilateral ulnar nerve (UN), median nerve (MN), radial nerve (RN), lateral popliteal (LPN) nerve, and posterior tibial nerve (PTN) to see the following parameters: Nerve thickening, echogenicity, color flow, and abscess. Results: The UN was most frequently involved followed by the PTN, MN, LPN, and RN. Diagnostic performance of HRUS for echogenicity was good with sensitivity, positive predictive value, and accuracy and was observed as 91.17%, 100%, and 91.17%, respectively. Conclusion: HRUS has several benefits in leprosy scanning; it is a reliable and non-invasive method of assessing alternations in the nerve at sites that may be difficult to be biopsied for histology.